A kind of corrosion-resistant composite refractory material and preparation method thereof

By using silicone modified phenolic resin as a binder and combining specific inorganic powder materials, the problem of insufficient corrosion resistance and thermal stability of refractory materials in low-quality coal gasification environment is solved, and the mechanics of composite refractory materials are significantly improved Performance and corrosion resistance.

CN117003553BActive Publication Date: 2024-12-17JIYUAN REFRACTORY FURNACE CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310996378.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2024-12-17
Estimated Expiration
2043-08-09

AI Technical Summary

Technical Problem

The existing refractory materials have poor corrosion resistance and insufficient thermal stability and mechanical strength in low-quality coal gasification environments. In particular, the thermal stability of seaweed extracts as binding agents are poor, which affects the overall performance of the material.

Method used

Using silicone modified phenolic resin as the binder, composite refractory materials are prepared through specific synthesis routes and process steps, including corundum fine powder, α-Al2O3 fine powder, silicon fine powder, clay, fused silica fine powder, wax fine powder, and sine Alcohol and water, combined with silicone modified phenolic resin, improve the thermal stability and adhesion of the material.

Benefits of technology

The corrosion resistance, mechanical strength, bulk density and thermal stability of composite refractory materials are significantly improved, the bonding strength between inorganic particles is enhanced, the viscosity is reduced, and the comprehensive performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004384772320000031
    Figure BDA0004384772320000031
  • Figure BDA0004384772320000051
    Figure BDA0004384772320000051
  • Figure BDA0004384772320000071
    Figure BDA0004384772320000071
Patent Text Reader

Abstract

This invention discloses a corrosion-resistant composite refractory material, comprising the following raw materials in parts by weight: 50-80 parts of fine corundum powder, 10-25 parts of α-Al₂O₃ micro powder, 6-12 parts of silica micro powder, 5-10 parts of clay, 2-5 parts of fine fused silica powder, 4-7 parts of fine pyrophyllite powder, 3-4 parts of octanol, 0.2-0.5 parts of water, and 3-5 parts of organosilicon-modified phenolic resin. The organosilicon-modified phenolic resin contains quinoline ring structures, siloxane structures, and boric acid structures, which endow it with excellent thermal stability, adhesion, and compatibility with inorganic particles, improving the bonding strength between the components of the inorganic refractory material, and significantly reducing the viscosity of the phenolic resin, thus improving its wettability to the inorganic refractory material. This invention also discloses a method for preparing this composite refractory material. The composite refractory material provided by this invention exhibits excellent corrosion resistance, mechanical strength, bulk density, and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a corrosion-resistant composite refractory material and a preparation method thereof. Background Art

[0002] Refractory materials are basic materials in the field of high-temperature technology, and their application fields are very wide. Among them, the most common application is as structural materials and linings to resist high temperatures in various thermal equipment and high-temperature containers. Statistical results show that the steel industry is the field that requires the most refractory materials, accounting for about 60% of the total output of refractory materials; the pyrometallurgy of non-ferrous metals and their thermal processing are also inseparable from refractory materials; the building materials industry and other high-temperature operating departments that produce silicate products, such as the glass industry, cement industry, and ceramic industry, all high-temperature furnaces or their linings need to be constructed with refractory materials; the water-coal slurry gasification device in the coal gasification field must also rely on refractory materials. Therefore, refractory materials need to have excellent corrosion resistance, thermal shock resistance, compressive strength, flexural strength and other properties.

[0003] The patent with application number CN201910649219.7 provides a composite refractory material, including the following raw materials: barium zirconate powder, penetrant, octanol, binder, yttrium oxide, calcium oxide, and zirconium dioxide. The refractory material is mixed by adding raw materials successively during the preparation process to reduce the agglomeration of raw materials and increase the contact area between the particles of each reactant. The obtained refractory product has high density. The synergistic effect of yttrium oxide, calcium oxide and zirconium dioxide can reduce the driving force of crack propagation and prevent crack propagation. With the help of corresponding heat treatment, the generation of bubbles and cracks in the material is reduced, and the yield and toughness of refractory products are improved. At the same time, by compounding the binder, octanol and penetrant, the sintering preparation process is easier to shape and the sintering temperature can be reduced. However, in the field of coal gasification, it has become an inevitable trend for the development of coal gasification to use low-quality coal as gasification raw material. Some low-quality coal contains a large amount of CaO and Na in its ash. 2 O.K 2 O and other alkali metal and alkaline earth metal oxides make the coal slag alkaline and significantly enhance its corrosiveness. When high chrome bricks are used in this environment, they are severely corroded by the slag. 6+The danger of generation. In order to improve the corrosion resistance of refractory materials, the patent with application number CN201510399047.4 provides a corrosion-resistant refractory material, including the following raw materials: alumina particles, α-alumina powder, nano-magnesia, zirconium oxide, graphene, additives, binders and nano-neodymium oxide. The refractory material provided by the invention has a high volume density, reduces its apparent porosity, and improves the strength, thermal shock resistance, impact resistance and other physical properties of the refractory material. By compounding graphene, the mechanical properties of the refractory products are guaranteed and the corrosion resistance of the refractory products is improved. However, the invention uses seaweed extract as a binder, and its preparation method is complicated and its thermal stability is poor. After high-temperature treatment, the bonding performance is significantly reduced, which will affect the comprehensive performance of the final refractory material. Therefore, there is an urgent need to develop a composite refractory material with good corrosion resistance, high thermal stability and excellent mechanical strength. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a corrosion-resistant composite refractory material having the characteristics of high mechanical strength, high bulk density, high thermal stability, excellent erosion resistance, etc. The present invention also provides a method for preparing the composite refractory material.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0006] A corrosion-resistant composite refractory material comprises the following raw materials in parts by weight: 50-80 parts of corundum fine powder, α-Al 2 O 3 10-25 parts of micropowder, 6-12 parts of silicon micropowder, 5-10 parts of clay, 2-5 parts of fused quartz fine powder, 4-7 parts of pyrophyllite fine powder, 3-4 parts of octanol, 0.2-0.5 parts of water, 3-5 parts of organosilicon-modified phenolic resin; the preparation method of the organosilicon-modified phenolic resin is as follows:

[0007] S1. Disperse 3-glycidyloxypropyltriethoxysilane in 2-methyltetrahydrofuran, add 2-(quinolin-3-yl)acetic acid and chromium acetate in sequence, heat to 70-80° C., stir for 7-11 hours, filter, take the filtrate, and distill under reduced pressure to obtain an intermediate;

[0008] S2, dispersing the intermediate obtained in step S1 and 3-hydroxyphenylacetic acid in 2-methyltetrahydrofuran, adding p-toluenesulfonic acid, heating to 65-80° C., stirring for 6-10 hours, filtering, taking the filtrate, distilling under reduced pressure, and drying to obtain organosilicon-modified phenol;

[0009] S3, under stirring conditions, heating phenol to 70-80°C, adding the organosilicon-modified phenol and boric acid obtained in step S2 in sequence, heating to 120-140°C, stirring for 2-3h, distilling under reduced pressure for 30-45min, cooling to 65-70°C, adding paraformaldehyde, and then heating to 120-140°C, stirring until the paraformaldehyde is completely dissolved, distilling under reduced pressure, and drying to obtain organosilicon-modified phenolic resin;

[0010] Wherein, the synthetic route of the organosilicon-modified phenol is as follows:

[0011]

[0012] The invention uses 3-glycidyloxypropyltriethoxysilane and 2-(quinolin-3-yl)acetic acid as raw materials, and under the action of chromium acetate, an epoxy compound undergoes a ring-opening reaction to obtain an intermediate; a hydroxyl group in the intermediate structure and a carboxyl group of 3-hydroxyphenylacetic acid undergo an esterification reaction under the action of p-toluenesulfonic acid to obtain an organosilicon-modified phenol; the organosilicon-modified phenol is mixed with phenol, and then a borate ester method is used to synthesize an organosilicon-modified phenolic resin.

[0013] In order to obtain organosilicon-modified phenol and ensure product consistency, the molar ratio of 3-glycidyloxypropyltriethoxysilane, 2-(quinolin-3-yl)acetic acid and chromium acetate in step S1 is 0.9-1.3:1:0.01-0.02, and the amount of 3-glycidyloxypropyltriethoxysilane added to the 2-methyltetrahydrofuran is 0.2-0.3 g / mL; the molar ratio of the intermediate, 3-hydroxyphenylacetic acid and p-toluenesulfonic acid in step S2 is 1:0.8-0.9:0.04-0.07, and the amount of 3-hydroxyphenylacetic acid added to the 2-methyltetrahydrofuran is 0.2-0.4 g / mL.

[0014] In order to synthesize the organosilicon-modified phenolic resin, increase the dispersibility and adhesion of the resin, and achieve the dual effects of adhesion and isolation, the mass ratio of phenol, organosilicon-modified phenol, boric acid and polyformaldehyde in step S3 is 85-95:5-15:18-20:40-45.

[0015] Preferably, the particle size of the corundum fine powder is ≤180 mesh, α-Al 2 O 3 The particle size of micro powder is ≤500 mesh, the particle size of clay, fused quartz fine powder, pyrophyllite fine powder is ≤180 mesh, and the particle size of silica micro powder is ≤800 mesh.

[0016] The present invention also provides a method for preparing a corrosion-resistant composite refractory material, comprising the following steps:

[0017] (1) Octanol, water and organosilicon-modified phenolic resin are uniformly mixed and stirred for 30-40 minutes to obtain a mixed material 1; corundum fine powder, α-Al 2 O 3 The micro powder, silicon micro powder, clay, fused quartz fine powder and pyrophyllite fine powder are uniformly mixed to obtain a mixed material 2; under stirring conditions, the mixed material 2 is added to the mixed material 1, and the stirring is continued for 30-40 minutes;

[0018] (2) The product obtained in step (1) is allowed to stand for 7-10 hours, and after drying, is placed in a vacuum furnace, kept at 1000-1100° C. for 10-15 minutes, and then kept at 1200-1400° C. for 2-4 hours, and cooled to room temperature in the furnace to obtain a composite refractory material.

[0019] The present invention has the following beneficial effects: the present invention obtains organosilicon-modified phenol by a two-step method, mixes the organosilicon-modified phenol with phenol, and then synthesizes the organosilicon-modified phenolic resin by a borate method, wherein the organosilicon-modified phenolic resin contains a quinoline ring structure, a siloxane structure and a boric acid structure, which can not only give it excellent thermal stability, adhesion and compatibility with inorganic particles, improve the bonding strength between various components of inorganic refractory materials, but also significantly reduce the viscosity of the phenolic resin and improve the wettability of the phenolic resin to the inorganic refractory materials. The composite refractory material provided by the present invention has excellent corrosion resistance, mechanical strength, bulk density and thermal stability. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application. The raw materials used in the following embodiments are all common commercially available products.

[0021] Example 1

[0022] A method for preparing an organosilicon-modified phenolic resin comprises the following steps:

[0023] S1. Disperse 3-glycidyloxypropyltriethoxysilane in 2-methyltetrahydrofuran, add 2-(quinoline-3-yl)acetic acid and chromium acetate in sequence, heat to 80°C, stir for 9h, filter, take the filtrate, and remove 2-methyltetrahydrofuran by distillation under reduced pressure to obtain an intermediate, wherein the molar ratio of 3-glycidyloxypropyltriethoxysilane, 2-(quinoline-3-yl)acetic acid and chromium acetate is 1:1:0.017, and the amount of 3-glycidyloxypropyltriethoxysilane added to 2-methyltetrahydrofuran is 0.2g / mL;

[0024] S2, dispersing the intermediate obtained in step S1 and 3-hydroxyphenylacetic acid in 2-methyltetrahydrofuran, adding p-toluenesulfonic acid, heating to 75°C, stirring for reaction for 8h, filtering, taking the filtrate, removing 2-methyltetrahydrofuran by reduced pressure distillation, and vacuum drying at 60°C for 24h to obtain organosilicon-modified phenol, wherein the molar ratio of the intermediate, 3-hydroxyphenylacetic acid and p-toluenesulfonic acid is 1:0.9:0.05, and the amount of 3-hydroxyphenylacetic acid added to 2-methyltetrahydrofuran is 0.3g / mL;

[0025] S3, under stirring conditions, heating phenol to 80°C, adding the organosilicon-modified phenol and boric acid obtained in step S2 in sequence, heating to 140°C, stirring for 2h, distilling under reduced pressure for 30min, removing part of the water, cooling to 70°C, adding paraformaldehyde, and then heating to 140°C, continuing to stir until the paraformaldehyde is completely dissolved, distilling under reduced pressure to remove the generated water, and vacuum drying at 60°C for 24h to obtain an organosilicon-modified phenolic resin, wherein the mass ratio of phenol, organosilicon-modified phenol, boric acid and paraformaldehyde is 90:10:19:43;

[0026] Wherein, the synthetic route of the organosilicon-modified phenol is as follows:

[0027]

[0028] The NMR results of silicone-modified phenol are: 1 HNMR (300 MHz, CDCl 3 )δ9.29(s, 1H), 8.76(s, 1H), 8.19(s, 1H), 8.07(d, 1H), 7.71(d, 1H), 7.49 -7.52(m, 2H), 6.98-7.05(m, 3H), 6.80(d, 1H), 5.40-5.46(m, 1H), 4.40-4. 42(m, 1H), 4.16-4.18(m, 1H), 3.80-3.84(m, 6H), 3.71(d, 3H), 3.53(s, 2H ), 3.45(d, 1H), 3.33(t, 2H), 1.41-1.44(m, 2H), 1.21(t, 9H), 0.56(t, 2H).

[0029] Example 2

[0030] A corrosion-resistant composite refractory material comprises the following raw materials in parts by weight: 75 parts of corundum fine powder, α-Al 2 O 320 parts of micropowder, 9 parts of silicon micropowder, 8 parts of clay, 4 parts of fused quartz fine powder, 6 parts of pyrophyllite fine powder, 3 parts of octanol, 0.4 parts of water, 4 parts of the organosilicon-modified phenolic resin prepared in Example 1; wherein the corundum fine powder is white corundum fine powder with a particle size of ≤180 mesh, α-Al 2 O 3 The particle size of micro powder is ≤500 mesh, the particle size of clay, fused quartz fine powder and pyrophyllite fine powder is ≤180 mesh, and the silica micro powder is grade 95 silica micro powder with a particle size ≤800 mesh.

[0031] A method for preparing a corrosion-resistant composite refractory material comprises the following steps:

[0032] (1) Octanol, water and organosilicon-modified phenolic resin were mixed evenly and stirred for 30 minutes to obtain a mixed material 1; corundum fine powder, α-Al 2 O 3 The micro powder, silica powder, clay, fused quartz fine powder and pyrophyllite fine powder are uniformly mixed to obtain a mixture 2; under stirring conditions, the mixture 2 is added to the mixture 1, and the stirring is continued for 30 minutes;

[0033] (2) The product obtained in step (1) was allowed to stand for 10 hours, dried at 200°C for 48 hours, placed in a vacuum furnace, heated to 1000°C at 5°C / min, kept warm for 15 minutes, then heated to 1400°C at 3°C / min, kept warm for 3 hours, and cooled to room temperature in the furnace to obtain a composite refractory material.

[0034] Example 3

[0035] A corrosion-resistant composite refractory material comprises the following raw materials in parts by weight: 75 parts of corundum fine powder, α-Al 2 O 3 20 parts of micro powder, 9 parts of silicon micro powder, 8 parts of clay, 4 parts of fused quartz fine powder, 6 parts of pyrophyllite fine powder, 3 parts of octanol, 0.4 parts of water, 3 parts of the organosilicon-modified phenolic resin prepared in Example 1; wherein the corundum fine powder is white corundum fine powder with a particle size of ≤180 mesh, α-Al 2 O 3 The particle size of the micropowder is ≤500 mesh, the particle size of the clay, fused quartz fine powder and pyrophyllite fine powder is ≤180 mesh, and the silicon micropowder is 95 grade silicon micropowder with a particle size of ≤800 mesh; the difference from Example 2 is that the weight portion of the organosilicon-modified phenolic resin is changed to 3 parts.

[0036] Example 4

[0037] A corrosion-resistant composite refractory material comprises the following raw materials in parts by weight: 75 parts of corundum fine powder, α-Al 2 O 320 parts of micropowder, 9 parts of silicon micropowder, 8 parts of clay, 4 parts of fused quartz fine powder, 6 parts of pyrophyllite fine powder, 3 parts of octanol, 0.4 parts of water, 5 parts of the organosilicon-modified phenolic resin prepared in Example 1; wherein the corundum fine powder is white corundum fine powder with a particle size of ≤180 mesh, α-Al 2 O 3 The particle size of the micropowder is ≤500 mesh, the particle size of the clay, fused quartz fine powder and pyrophyllite fine powder is ≤180 mesh, and the silicon micropowder is 95 grade silicon micropowder with a particle size of ≤800 mesh; the difference from Example 2 is that the weight portion of the organosilicon-modified phenolic resin is changed to 5 parts.

[0038] Comparative Example 1

[0039] A corrosion-resistant composite refractory material comprises the following raw materials in parts by weight: 75 parts of corundum fine powder, α-Al 2 O 3 20 parts of micro powder, 9 parts of silicon micro powder, 8 parts of clay, 4 parts of fused quartz fine powder, 6 parts of pyrophyllite fine powder, 3 parts of octanol, 0.4 parts of water, 1 part of phenolic resin; wherein the corundum fine powder is white corundum fine powder, with a particle size of ≤180 mesh, α-Al 2 O 3 The particle size of the micropowder is ≤500 mesh, the particle size of the clay, fused quartz fine powder, and pyrophyllite fine powder is ≤180 mesh, and the silicon micropowder is 95 grade silicon micropowder with a particle size ≤800 mesh; the difference from Example 2 is that the organosilicon-modified phenolic resin is replaced by phenolic resin (model 2123, purchased from Jinan Dahui Chemical Technology Co., Ltd.).

[0040] Comparative Example 2

[0041] A corrosion-resistant composite refractory material comprises the following raw materials in parts by weight: 75 parts of corundum fine powder, α-Al 2 O 3 20 parts of micro powder, 9 parts of silicon micro powder, 8 parts of clay, 4 parts of fused quartz fine powder, 6 parts of pyrophyllite fine powder, 3 parts of octanol; wherein the corundum fine powder is white corundum fine powder, with a particle size of ≤180 mesh, α-Al 2 O 3 The particle size of the micro powder is ≤500 mesh, the particle size of the clay, fused quartz fine powder and pyrophyllite fine powder is ≤180 mesh, and the silicon micro powder is 95 grade silicon micro powder with a particle size of ≤800 mesh; the difference from Example 2 is that: no organosilicon-modified phenolic resin and water are added.

[0042] The corrosion-resistant composite refractory materials described in Examples 3-4 and Comparative Examples 1-2 were all prepared according to the method described in Example 2.

[0043] The composite refractory materials prepared in Examples 2-4 and Comparative Examples 1-2 were made into 40mm×40mm×160mm specimens, and relevant performance tests were performed. The compressive strength test was performed in accordance with GB / T5072-2008 "Test Method for Compressive Strength of Refractory Materials at Room Temperature"; the bulk density test was performed in accordance with GB / T2997-2015 "Test Method for Bulk Density and True Porosity of Dense Shaped Refractory Products"; the flexural strength test was performed in accordance with GB / T3001-2007 "Test Method for Flexural Strength of Refractory Materials at Room Temperature"; the permanent line change rate test was performed in accordance with GB / T5988-2022 "Test Method for Permanent Line Change of Refractory Materials Heating"; For the thermal shock stability test, the sample was placed in a test furnace at 1100°C, kept warm for 20 minutes, immersed in running water for one minute, and then taken out and placed in the air for 5 minutes. This cycle was repeated ten times. After the sample was dried, the room temperature flexural strength of the sample after the thermal shock test was tested, and the flexural strength retention rate of the sample was calculated. The load softening temperature test was carried out in accordance with GB / T5989-2008 "Refractories Load Softening Temperature Test Method Differential Heating Method"; the corrosion resistance test experimental conditions: 1400°C × 3h, the etchant is Na 2 CO 3 (10g), excessive NaOH ("alkali cracking" refers to cracks that can be observed by naked eyes without the aid of a microscope); the results are shown in Table 1. It can be seen from the table that the compressive strength, flexural strength, permanent linear change rate, bulk density, load softening temperature, thermal shock stability and corrosion resistance of the composite refractory prepared in Examples 2-4 are significantly better than those in Comparative Examples 1-2, among which the composite refractory prepared in Example 2 has the best comprehensive performance; compared with Comparative Examples 1-2, the addition of organosilicon-modified phenolic resin can significantly improve the comprehensive performance of the composite refractory.

[0044] Table 1 Composite refractory material performance test results

[0045]

[0046]

[0047] The organosilicon-modified phenolic resin provided by the present invention contains a quinoline ring structure, a siloxane structure and a boric acid structure, which can not only give it excellent thermal stability, adhesion and compatibility with inorganic particles, improve the bonding strength between the components of the inorganic refractory material, but also significantly reduce the viscosity of the phenolic resin and improve the wettability of the phenolic resin to the inorganic refractory material. The composite refractory material provided by the present invention has excellent corrosion resistance, mechanical strength, bulk density and thermal stability.

[0048] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A corrosion-resistant composite refractory material, characterized in that: The raw materials include the following parts by weight: 50-80 parts of corundum fine powder, 10-25 parts of α-Al2O3 fine powder, 6-12 parts of silicon fine powder, 5-10 parts of clay, 2-5 parts of fused quartz fine powder, 4-7 parts of pyrophyllite fine powder, 3-4 parts of octanol, 0.2-0.5 parts of water, and 3-5 parts of organosilicon-modified phenolic resin; the preparation method of the organosilicon-modified phenolic resin is as follows: S1. Disperse 3-glycidyloxypropyltriethoxysilane in 2-methyltetrahydrofuran, add 2-(quinolin-3-yl)acetic acid and chromium acetate in sequence, raise the temperature to 70-80°C, stir for 7-11h, filter, take the filtrate, and distill under reduced pressure to obtain an intermediate. The structural formula of the intermediate is: S2. Disperse the intermediate obtained in step S1 and 3-hydroxyphenylacetic acid in 2-methyltetrahydrofuran, add p-toluenesulfonic acid, raise the temperature to 65-80° C., stir for 6-10 hours, filter, take the filtrate, distill under reduced pressure, and dry to obtain organosilicon-modified phenol. The structural formula of organosilicon-modified phenol is: S3, under stirring conditions, heating phenol to 70-80°C, adding the organosilicon-modified phenol and boric acid obtained in step S2 in sequence, heating to 120-140°C, stirring for 2-3h, distilling under reduced pressure for 30-45min, cooling to 65-70°C, adding paraformaldehyde, and then heating to 120-140°C, stirring until the paraformaldehyde is completely dissolved, distilling under reduced pressure, and drying to obtain organosilicon-modified phenolic resin; The molar ratio of 3-glycidyloxypropyltriethoxysilane, 2-(quinolin-3-yl)acetic acid and chromium acetate in step S1 is 0.9-1.3:1:0.01-0.02; The amount of 3-glycidyloxypropyltriethoxysilane added to the 2-methyltetrahydrofuran is 0.2-0.3 g / mL; The molar ratio of the intermediate, 3-hydroxyphenylacetic acid and p-toluenesulfonic acid in step S2 is 1:0.8-0.9:0.04-0.07; The amount of 3-hydroxyphenylacetic acid added to the 2-methyltetrahydrofuran is 0.2-0.4 g / mL.

2. The corrosion-resistant composite refractory material according to claim 1, characterized in that: The mass ratio of phenol, organosilicon-modified phenol, boric acid and paraformaldehyde in step S3 is 85-95:5-15:18-20:40-45.

3. The corrosion-resistant composite refractory material according to claim 1, characterized in that: The particle size of the corundum fine powder is ≤180 mesh, the particle size of the α-Al2O3 fine powder is ≤500 mesh, the particle size of the clay, fused quartz fine powder, and pyrophyllite fine powder is ≤180 mesh, and the particle size of the silicon fine powder is ≤800 mesh.

4. A method for preparing a corrosion-resistant composite refractory material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) octanol, water and organosilicon-modified phenolic resin are uniformly mixed and stirred for 30-40 minutes to obtain a mixed material 1; corundum fine powder, α-Al2O3 fine powder, silicon fine powder, clay, fused quartz fine powder and pyrophyllite fine powder are uniformly mixed to obtain a mixed material 2; under stirring conditions, the mixed material 2 is added to the mixed material 1 and the stirring is continued for 30-40 minutes; (2) The product obtained in step (1) is allowed to stand for 7-10 hours, and after drying, is placed in a vacuum furnace, kept at 1000-1100° C. for 10-15 minutes, and then kept at 1200-1400° C. for 2-4 hours, and cooled to room temperature in the furnace to obtain a composite refractory material.

Citation Information

Patent Citations

  • A kind of corrosion-resistant refractory material and preparation method thereof

    CN105036716B

  • Composite refractory material and preparation method thereof

    CN110156463A

  • Superior-performance blast furnace connector material

    CN106747514A

  • Preparation method for synthesizing organic silicon modified phenolic resin by ester exchange method

    CN110591029A